Structure, Microstructure And Superconductivity Of Yba2cu3o7-I With Magnetic Nanoparticle Additives - Mansor, Mohd Kamarulzaman (2010)

(untitled)
Potential enhancement of flux pinning by rare-earth (RE) magnetic nanoparticles added into bulk of YBa2Cu3O7-8 (YBCO) was studied experimentally. In particular, a comprehensive investigation of crystal structure, microstructure and superconducting properties of YBCO added with x weight percent (x = 0.0 - 0.6 wt. %) of nanosized (< 25 nm) Nd2O3, Sm2O3, Gd2O3 and Yb2O3 prepared via solid state technique was presented. X-ray diffraction (XRD) technique was used for crystal structure and phase formation identification. Detailed crystal structure analysis was carried out on each sample using the Rietveld refinement technique. The fractured cross section microstructure was observed using Scanning Electron Microscopy (SEM) and support by elemental analysis using Energy Dispersive X-ray (EDX) spectroscopy. Four point probe technique were employed to study the resistance dependence from room temperature down to 50 K. The XRD patterns revealed that only YBCO phase peaks were observed for sample with x < 0.3 and minor intensities of 211 secondary phase was observed for x > 0.4 in each series.